The Influence of Time-Out Applied by Parents toward Students’ Intensity in Playing Game - Muhammad Aenul Yaqin; Mariyam Mariyam (Universitas Muhammadiyah Semarang, 2020)
The impact of online game dependence includes aggressive behavior, lack of respect for other people, and threatening persecution. Playing games will not be controlled if parents do not supervise or set limits. Time out is expected to reduce the intensity of playing online games in school-age children. This study aims to determine the effect of time out by parents on the intensity of playing games in school-age children. The design of this study was an experiment with one group pre-test post-test. Respondents were 50 parents with school-age children who had moderate and high-intensity games. Time out interventions (isolation time out) are carried out by parents with a time adjusting the child's age, carried out for 5 days. The intensity of gameplay describes the duration of gameplay in a day, the classification is low, moderate, and high. The results showed that the intensity of playing games before being given time out was mostly in high classification (54%). Statistical test results indicate that there is a time out by parents of the intensity of playing games in school-age children (p= 0.0001).